Porfiria aguda en el embarazo: diagnóstico y manejo - Sepúlveda M, Alvaro; Hasbún F., Jorge (Revista Hospital Clínico Universidad de Chile, 2009)
Intermittent acute porphyria during pregnancy is a rare disease. Due to its capacity to simulate an acute abdomen without any apparent cause, it requires an accurate diagnosis and a specific management. This review will present the epidemiology, physiopathology, classification, specific diagnostic criteria and management, focusing on the triggering factors and drugs contraindicated in this diagnosis.